Review of the transmission of sound from air to water - H. W. JONES; H. W. KWAN (Archives of Acoustics, 2015)
This paper reviews the physical principles relating to the transmission of sound from air to water. The major emphasis is on the effect of the air-water interface on the transmission of sound to an underwater receiver. A limited consideration only is given to non-flat surfaces and the transmission at grazing angles of incidence.